2013
DOI: 10.1136/acupmed-2013-010324
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Review of the Electroacupuncture Literature: Clinical Applications and Endorphin Mechanisms

Abstract: Electroacupuncture (EA) is widely used in clinical practice and research, as well as in experimental investigations into the mechanisms of acupuncture. This study explores publication trends in clinical and experimental studies of EA (1975EA ( -2011 for pain and non-pain research; EA use for different clinical conditions ; and the relation of EA research, including stimulation frequency, to opioid peptide mechanisms. Appropriate PubMed 'all fields' searches were conducted, identified studies were classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 22 publications
2
50
0
3
Order By: Relevance
“…Previous studies have suggested that different frequencies of EA can induce different peripheral reactions [18, 19], but little effort has been made to investigate how EA with different intensities affects jejunal motility.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that different frequencies of EA can induce different peripheral reactions [18, 19], but little effort has been made to investigate how EA with different intensities affects jejunal motility.…”
Section: Introductionmentioning
confidence: 99%
“…Mayor 35 argues that EA implicitly provides a greater dose of stimulation compared to MA alone, based on greater activation of endogenous opioid mechanisms (EOM). The single trial comparing MA with EA showed a more rapid onset of pain relief in the EA group.…”
Section: Immediatementioning
confidence: 99%
“…Acupuncture may reduce endometriosis-related CPP through multiple mechanisms including the potential to reduce prostaglandin expression [18], reduce nerve growth factor [19], increase endogenous opioid release [20] and reduce mechanical allodynia [19]. However, the effects of acupuncture on three key areas that are altered in women with chronic pelvic pain are still unclear: increased inflammatory markers, changes in neuronal functional connectivity, and altered endogenous pain modulation.…”
Section: Introductionmentioning
confidence: 99%